THE WEB-ORIENTED CONSTRUCTIVISM INSTRUCTION APPROACH TO IMPROVE STUDENT’S HABITS OF MIND - Ida Yayu Nurul Hizqiyah; Siti Sriyati; Dini Riyani; Saiman Rosamsi (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2019)
The purposes of this study to determine whether the web-oriented constructivism instruction approach can improve student’s habits of mind on the biodiversity concept. The method used in the study is  pre experiment method with one-grup pretest-posttest design who appied to students X-MIA 6 class and total 38 students. Research data is collected using critical thinking test, creative thinking test, self regulationquistionnare, and contributes  a web-oriented constructivism instruction approach to habits of mind observation sheet. Data were analyzed using hypothesis test and gain calculation. The result of this study that there are significant differences in student’s habits of mind score between before and after being applied the web-oriented constructivism instruction approach, and if based on the results of gain calculation, it was found that the most student an increase in the  medium on gain category. Other than that, if judging from the contributes  a web-oriented constructivism instruction approach to habits of mind category  it was found the results of a very good interpretation. Key Word: Web-oriented constructivism instruction approach, Habits of mind category